Influence of genotypes, stages of microspore, pre-treatments and media factors on induction of callus from anthers of cocoa (Theobroma cacao L.) - D. Sudhakar, J. Suresh, R. Sivachandran, R. Gnanam; Ganesh Ram, S. (Journal of Plantation Crops, 2017)
In vitro anther culture in cocoa will be useful for the production of homozygous line to accelerate breeding programs. The efficiency of callus induction and plant regeneration are highly dependent on genotypes and other physiological factors. The influence of genotypes, pre-treatments and medium combinations were examined with anthers isolated from two different flower bud sizes (2 to 3 and 4 to 6 mm long representing uni-nucleate and bi-nucleate microspore development stages, respectively) during androgenesis. Anthers isolated from 2 to 3 mm long flower buds, both fresh and cold pre-treated, were found to have good callus induction than gamma irradiated. Anthers of CCRP 1 genotype recorded highest percentage of callus induction in CIM 4 medium compared to other genotypes and medium combinations with both flower bud sizes. Anthers from 4 to 6 mm long flower buds showed better callus induction response in fresh and gamma irradiated than cold pre-treated flower buds. However, 2 to 3 mm long flower buds were superior to 4 to 6 mm long flower buds for callus induction. Maximum callus induction frequencies for CCRP 1 and CCRP 5 were obtained from 2 to 3 mm long flower bud in DKW medium supplemented with glutamine (250 mgL-1), myo-inositol (200 mg L-1), 2,4-D (2 mg L-1), TDZ (10 ìg L-1), and glucose (20g L-1) in pre-treated flower buds (either with cold or gamma irradiated). However, the combined interaction effect between genotypes, pre-treatments and medium combinations had no significant influence on callus induction when 2 to 3 mm long flower buds were used. The development of different callus morphotypes viz., friable/embryogenic, watery, compact, hairy and rhizogenic has been observed in this study. In addition, greening of calli was also noticed.These findings would be valuable for regeneration and development of haploid cocoa plants in future.